(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Upper and lower GI endoscopy are the most exigent procedure to diagnose various diseases in gastroenterology. Acceptability and tolerability of Endoscopy are variable due to its way of approach to the individuals. Negative attitude towards these procedures can be overcome by proper motivation of patients regarding importance of the tests and also by explaining the additional sideeffects of sedatives, cost and time to spend for tests. Objective: The aim of this study was undertaken to see the attitude, response during procedure, easiness of finding lesions and completeness of these procedures without sedation. Methodology: This was a cross-section study. Samples were collected purposively of whom age were between 13 and 65 of either sex and who underwent Upper and Lower GI procedures in the department of Gastroenterology, Shaheed Suhrawardy Medical Hospital from January 2016 to October 2016. This study was approved by the Ethical review board of Shaheed Suhrawardy Medical College. Results: Among 1205 patients, 724 (Upper GI 663 and lower GI 61) patients were male and 481 (Upper GI 433 and lower GI 48) were female. 58.26% patients showed positive attitude towards GI procedures through both upper and lower route. 57.61% male and 46.19% female well tolerated upper GI endoscopy, whereas 37.70% male and 43.75% female tolerated lower GI endoscopy. Procedures were successfully completed in 97.89 % male and 97.22% female patients of UGI and 96.72 male and 85.42% female patients of LGI endoscopy without sedation. Conclusion: Endoscopy of both upper and lower gastrointestinal tract can safely and effectively be done without sedation. Journal of National Institute of Neurosciences Bangladesh, 2018;4(2): 141-144